Success Rate and Safety of Ultrasound-Guided Supraclavicular Brachial Plexus Blocks; A Retrospective Study of 1,830 Cases - Sinthuprasit, Wanwisa (Thai Journal of Anesthesiology, 2021)
Background: Currently, the supraclavicular brachial plexus block ultrasound-guided technique is used to replace the paresthesia technique. The technique allows the visualization of the needle and the distribution of anesthetic around the nerves. It reduces the duration of the procedure and complications following the procedures. Objective: To study the success and complications of ultrasound-guided supraclavicular brachial plexus blocks in Khon Kaen Hospital. Methods:A study of the patients who received ultrasoundguided supraclavicular brachial plexus blocks for arm, wrist, and hand surgery at Khon Kaen Hospital from 2017 to 2019. The data was collected on success, and complications following the procedure, type and amount of local anesthesia used, and the supplemental medication that the patient receives. Results: A total of 1,830 patients, 1,660 patients (90.71%) were classified as successful, while 184 patients (9.92%) were classified as failed, of which 91 patients received an additional nerve block 31 patients received ulnar nerve block, 46 patients received axillary nerve block, and 93 patients (5.08%) switched to general anesthesia. A total of 434 patients (26.14%) received additional supplemental therapy which the most commonly used medications were 0.5%bupivacaine or 0.5%levobupivacaine mixed with 2% lidocaine with adrenalin 1:200,000. The dose was 15-35 millimeters without complications in this study. Conclusion: The ultrasound-guided supraclavicular brachial plexus blocks had a high success rate (90.71%) and reduced the likelihood of complications following the procedures.